Spherical Harmonics Scaling - Zhou, Kun; Wang, Jiaping; Lin, Steve; Guo, Baining (The Visual Computer, 2006)
A method, device and system is provided for providing global illumination of a scene. For example, global illumination may be provided in a rendered 3-dimensional image that may contain objects and/or light sources. Radiance functions or visibility functions may further be represented by scaling of spherical harmonics functions in the spherical harmonics domain. For example, scaling of spherical harmonics coefficients corresponding to a spherical function may be performed based on a spherical harmonics scaling transformation matrix based on an angular scaling function.
US Patent 7,663,623 B2